GERAKAN AGAMAISASI DI KAWASAN MENOREH YOGYAKARTA Sebuah Kajian Antropologi Sastra - Suwardi, Suwardi (Analisis: Jurnal Studi Keislaman, 2013)
div style="text-align: justify;">This article aims to understand phenomena in the region agamaisasi Menoreh Yogyakarta. Agamaisasi is the official religion of the hegemony of the movement against the original religion (belief).  To delve deeper study  of the  state’s  use of literary anthropology. Pemabahasan this kind of glass can be used as observers of Bengal for religious, cultural, and political. Results found, it indicates that the movement should occur in the system agamaisasi social culture in Yogyakarta  Menoreh region.   Agamaisasi   occurs   because   the   original   religion (belief  penghayat)  considers to be the official religion of his burden. Agamaisasi result,  there  appears to  be a fierce feud between modern Islam and immigrants with native religion or religious identity  cards. Efforts official religion of modernity which requires renewal of religious behavior in a way to leave tradition, considered to be a religious burden. Associated with splashy agamaisasi, area residents Menoreh Yogyakarta choose berfalsafah sit under a banana tree. That is, it is better  to live once useful to others. <